2000
DOI: 10.1190/1.1444812
|View full text |Cite
|
Sign up to set email alerts
|

Kirchhoff modeling, inversion for reflectivity, and subsurface illumination

Abstract: Because of its computational efficiency, prestack Kirchhoff depth migration is currently one of the most popular algorithms used in 2-D and 3-D subsurface depth imaging. Nevertheless, Kirchhoff algorithms in their typical implementation produce less than ideal results in complex terranes where multipathing from the surface to a given image point may occur, and beneath fast carbonates, salt, or volcanics through which raytheoretical energy cannot penetrate to illuminate underlying slower-velocity sediments. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(69 citation statements)
references
References 26 publications
0
69
0
Order By: Relevance
“…The least-squares migration method (Lailly, 1984;Cole and Karrenbach, 1992;Schuster, 1993;Nemeth et al, 1999;Duquet et al, 2000) has been shown to sometimes produce migration images with better quality than those computed by conventional migration. When least-squares migration is implemented with the RTM method (Tang and Biondi, 2009;Dai and Schuster, 2010a;Dai et al, 2010;Wong et al, 2011;Dai et al, 2012), it can reduce not only the acquisition footprint but also the artifacts in the RTM image, while enhancing the image resolution.…”
Section: Chapter 2: Multisource Least-squares Reverse Time Migrationmentioning
confidence: 99%
See 4 more Smart Citations
“…The least-squares migration method (Lailly, 1984;Cole and Karrenbach, 1992;Schuster, 1993;Nemeth et al, 1999;Duquet et al, 2000) has been shown to sometimes produce migration images with better quality than those computed by conventional migration. When least-squares migration is implemented with the RTM method (Tang and Biondi, 2009;Dai and Schuster, 2010a;Dai et al, 2010;Wong et al, 2011;Dai et al, 2012), it can reduce not only the acquisition footprint but also the artifacts in the RTM image, while enhancing the image resolution.…”
Section: Chapter 2: Multisource Least-squares Reverse Time Migrationmentioning
confidence: 99%
“…Least-squares migration was originally implemented with Kirchhoff migration (KM) method (Nemeth et al, 1999;Duquet et al, 2000), but was later developed for phase shift migration algorithms (Kaplan et al, 2010;Huang and Schuster, 2012a). In this dissertation, I propose to implement LSM with reverse time migration (RTM) (Baysal et al, 1983;Whitmore, 1983;McMechan, 1983), where the Green's functions are calculated by finite-difference solution to the full wave equation instead of asymtotic Green's function in Kirchhoff migration (Bleistein, 1987), or one-way solution in one-way wave equation migration (Claerbout, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations